Violence in the workplace : prevention guide - Canadian Centre for Occupational Health and Safety, Hamilton (Hamilton, 2001)
"The Violence in the Workplace Prevention Guide provides workers, employers, health and safety professionals plus human resources professionals with detailed guidance on how they can develop workplace violence prevention programs. The Guide includes specific tips on a multitude of workplace and work-related travel situations, as well as practical advice on how people should respond to specific violent situations. As with the first edition, this completely up-to-date, practical guide provides readers with easy-to-follow checklists and guidelines. The Violence in the Workplace Prevention Guide uses workplace situations rather than specific occupations or business sectors to illustrate prevention and response content. This unique approach allows organizations to fully customize their violence prevention program based on the results of their overall risk assessment and to develop a prevention program that directly applies to their work environment. Some violence prevention initiatives that CCOHS clients have successfully implemented include: procedures for reporting and investigating incidents; critical incident management; victim support services; and, training programs." (From the Press release)